Notes on the distribution of the genus Pseudopaludicola Miranda-Ribeiro, 1926 (Anura: Leptodactylidae) in Paraguay - Lavilla, Esteban Orlando (2016)
Four species of Pseudopaludicola, Pseudopaludicolaboliviana, P. falcipes, P. mystacalis and P. ternetzi, areusually cited for Paraguay. However, after analyzing 407specimens assigned to this genus in herpetological collectionsof the country, we conclude that there are nospecimens of P. falcipes in Paraguayan collections orvouchers cited in the literature, and almost all individualsreferred to P. ternetzi are most probably P. ameghini.At the same time, a recently described species, P. motorzinho,is recorded for the first time in the country. Informationon the distribution of these and the remainingspecies of Pseudopaludicola in Paraguay (P. boliviana andP. mystacalis) is provided.